Significance of foreign direct investment in the economic development of Lower Silesia 1989-2005 - Popławski, Maciej (Wydawnictwo Uniwersytetu Wrocławskiego, 2008)
The article is an attempt at estimating the significance of foreign direct investment in the economic development of Lower Silesia 1989–2005. The article consists of three main chapters: The inflow and location of FDI in Lower Silesia, the influence of FDI on economic development of Lower Silesia and advantages and negative outcomes of foreign capital inflow to Lower Silesia. The first chapter consists of six parts: an evolution of the FDI inflow in the areas and regions of Poland; main reasons of the inflow to Lower Silesia (including investment attractiveness of the region and significance of special economic zones for the FDI inflow); location of FDI in subregions of Lower Silesia, phases of FDI inflow to Lower Silesia according to the number of companies and the value of foreign capital, structure of FDI inflow (including types of commercial law companies according to legal forms, value of the country and its origins, types of activity according to branches, countries of origin and the income). The chapter performs an exact analysis of Wrocław agglomeration: conditions and phases, changes in structure, Wrocław as compared with city agglomerations in Poland and outcomes of foreign capital inflow to the city. The second chapter is an attempt at pointing the influence of FDI on economic development of Lower Silesia. It consist of six parts: investment expenditure of FDI in the region, an influence of FDI on the work market, level of employment and unemployment, exports and imports of foreign capital companies, extension of innovation and organizational-technological development, the impact on the economic level development and the influence on the economy in Lower Silesia in the process of privatization. The last chapter outlines advantages and negative outcomes of foreign capital inflow to Lower Silesia.
Keywords: bezpośrednie inwestycje zagraniczne; Dolny Śląsk; rozwój lokalny